(untitled) (Journal of Nepal Geological Society, 2000)
Dimension stone exploitation in the Ossola Basin, one of the biggest in Italy, is strongly influenced by the orientation and spacing of discontinuities as well as the topography of the quarry site. Exploitation techniques too are often affected by these critical conditions. In the paper, the rock properties affecting the exploitation and the most useful splitting techniques are discussed. An example of the application of the exploitation method is also given.